2003
DOI: 10.1074/jbc.m210496200
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli RecX Inhibits RecA Recombinase and Coprotease Activities in Vitro and in Vivo

Abstract: In Escherichia coli the RecA protein plays a pivotal role in homologous recombination, DNA repair, and SOS repair and mutagenesis. A gene designated recX (or oraA) is present directly downstream of recA in E. coli; however, the function of RecX is unknown. In this work we demonstrated interaction of RecX and RecA in a yeast two-hybrid assay. In vitro, substoichiometric amounts of RecX strongly inhibited both RecA-mediated DNA strand exchange and RecA ATPase activity. In vivo, we showed that recX is under contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
172
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(182 citation statements)
references
References 42 publications
9
172
0
1
Order By: Relevance
“…The effect of RecX is actually greater where RecX protein is added to an experiment prior to RecA protein (52). The inhibition of RecA ATPase activity by RecX is greater in the presence of SSB than in the absence of SSB (58).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The effect of RecX is actually greater where RecX protein is added to an experiment prior to RecA protein (52). The inhibition of RecA ATPase activity by RecX is greater in the presence of SSB than in the absence of SSB (58).…”
mentioning
confidence: 92%
“…The RecX protein is the focus of the present report and an inhibitor of RecA function both in vivo and in vitro (58). Seifert and co-workers (58) demonstrated that RecA and RecX proteins physically interact using yeast two-hybrid analysis in E. coli.…”
mentioning
confidence: 99%
“…RecX is a bacterial regulatory protein which acts as an anti-recombinase to quell inappropriate recombinational repair during normal DNA metabolism [122,123]. It is found in bacteria and some plants (Arabidopsis thaliana & Oryza sativa) but not in archaea.…”
Section: Methanobacterium Thermoformicium and Neisseria Gonorhoeaementioning
confidence: 99%
“…The recX gene that is situated 161 bp downstream of the H. influenzae recA gene (an organization that is observed in several bacterial species) was also investigated. In E. coli, recX is cotranscribed with recA (Pagès et al, 2003) and inhibits recombinase, co-protease and ATP hydrolysis activities of RecA (Venkatesh et al, 2002;Pagès et al, 2003;Stohl et al, 2003), indicating that recX may play an important role in SOS responses.…”
Section: Northern Blot and Rt-pcr Analysis Of The Sos Responsementioning
confidence: 99%